Photoactivity of nanostructured porous Nb2O5: Effect of Pt, Ta, Cu, and Ti impregnation. Issue 6 (30th August 2022) - Antonini, Leonardo Marasca; Adamski, Janice; Bernardi, Fabiano; Aguzzoli, Cesar; Hübler, Roberto; de Fraga Malfatti, Célia
Abstract: In the present work, we report the obtaining of nanostructured porous Nb2 O5 by anodizing process, with Pt, Ta, Cu, or Ti impregnation, and by magnetron sputtering process. The techniques of scanning electron microscopy, X‐ray diffraction, and X‐ray photoelectron spectroscopy were used to evaluate the morphology, and the composition and crystalline structure of nanoporous Nb2 O5 . The photocatalytic activity was evaluated by electrochemical photocurrent tests under UV light illumination. Nanostructured porous Nb2 O5 with Pt, Ta, Cu, and Ti impregnation presented bandgap reduction and 10 times higher photocurrent density in the presence of UV light when compared to the not impregnated nanoporous Nb2 O5 . Abstract : Graphical Abstract: